কবিতার শামসুর রাহমান - রহমান, গাউসুর 1965- (ঢাকা : অরদন পাবলিকেশন, 2010)
Study on the works of Shamsur Rahman, Bengali poet from Bangladesh.
Includes bibliographical references and index.
"Śāmasura Rahamānera kābyagrantha": p. [403]-427.
In Bengali.
Keywords: Rāhamāna, Śāmasura, -- 1929-2006 -- Criticism and interpretation